Changes in coagulation markers in children with Mycoplasma pneumoniae pneumonia and their predictive value for Mycoplasma severity - Yong-tao Li; Ju Zhang; Meng-zhu Wang; Yu-Mei Ma; Ke Zhi; Fu-Li Dai; Shu-jun Li (BMC, 2023)
Abstract Background This study investigates the correlation between coagulation levels and the severity of Mycoplasma pneumoniae pneumonia (MPP) in children. In addition, the study analyses the predictive value of coagulation abnormalities in MPP combined with necrotising pneumonia (NP). Methods A total of 170 children with MPP who underwent treatment between June 2021 and February 2022 were selected for this study. The study population was divided into groups according to the severity of the disease to compare differences in the incidence of coagulation abnormalities between the groups. The participants were also divided into groups according to imaging manifestations to compare the differences in coagulation function among the different groups. All data information was processed for statistical analysis using SPSS Statistics 25.0 and GraphPad Prism 7.0 statistical analysis software. Results The incidence of coagulation abnormalities in the children in the severe MPP (SMPP) group was significantly higher than that in the normal MPP (NMPP) group (P < 0.05). The multi-factor logistic regression analysis revealed that the D-dimer level is an independent risk factor for the development of NP in SMPP (P < 0.05). The receiver operating characteristic curve analysis revealed statistically significant differences (P < 0.05) in D-dimer, fibrinogen degeneration products (FDP), neutrophils, lactate dehydrogenase and serum ferritin for predicting SMPP combined with NP. Bronchoscopic manifestations of coagulation indicators (D-dimer and FDP levels) were significantly higher in the mucus plug group than in the non-mucus plug group, while the activated partial thromboplastin time levels were lower in the former than in the latter (P < 0.05). Conclusion The degree of elevated D-dimer and FDP levels was positively correlated with the severity of MPP, with elevated serum D-dimer levels (> 3.705 mg/L) serving as an independent predictor of MPP combined with NP in children.